2019
DOI: 10.1111/1750-3841.14482
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Nutraceutical Composition of Pansies (Viola × wittrockiana) During Flowering

Abstract: Edible flowers consumption and use are an increasing food trend worldwide, although information concerning their nutritional composition and nutraceutical value is still scarce. Thus, the aim of this study was to contribute to the popularization of pansies (Viola × wittrockiana), through the analysis of the nutritional and nutraceutical features of pansies with different colors (white, yellow, and red) and flowering stages. Both flower type and flowering stage influenced the flower composition. When completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
(46 reference statements)
1
19
0
1
Order By: Relevance
“…Similar DPPH inhibition was found by González-Barrio et al in a V. x wittrockiana flower extract obtained by maceration (71.20%) [ 5 ]. Besides, our results seem to be better to the data obtained for V. x wittrockiana carried out by Fernandes et al [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 76%
“…Similar DPPH inhibition was found by González-Barrio et al in a V. x wittrockiana flower extract obtained by maceration (71.20%) [ 5 ]. Besides, our results seem to be better to the data obtained for V. x wittrockiana carried out by Fernandes et al [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 76%
“…They are also used in drinks (wine and beer), desserts, jellies, and spices [ 92 ]. Usually, some plants are known for the flavoring or nutritional potential of their fruits or leaves, while some flowers are also edible and rarely used in cooking, such as passion fruit, chive, and pumpkin [ 93 ]. Although the use of edible flowers is still in its infancy, flowers are a natural source of bioactive chemicals [ 94 ].…”
Section: Nutritional Value-added Plants and Their Role In Human Healthmentioning
confidence: 99%
“…The energy value observed in the flowers (19.02 ± 3.07 kcal 100 g -1 ) and in the roots (55.30 ± 2.49 kcal 100 g -1) , both on a fresh basis (Table 1), confirms the low-calorie content of this species, including when compared to other species whose flowers and roots are consumed. Pansy flowers (Viola × wittrockiana) showed energy values between 31 and 52 kcal 100 g -1 (Fernandes et al, 2019), Nasturtium flowers showed values between 34.32 kcal 100 g -1 and 72.79 kcal 100 g -1 (Lima Franzen et al, 2016). The caloric value of roots of dahlia was between that of clones of Leren (Calathea allouia (Aubl.)…”
Section: Percent Compositionmentioning
confidence: 99%